LCD Monitors as an Alternative for Precision Demanding Visual Psychophysical Experiments. (September 2016) - Bognár, Anna; Csibri, Péter; András, Csaba Márk; Sáry, Gyula
Precise timing and presentation of stimuli is critical in vision research, still, the limiting factor in successful recognition is often the monitor itself that is used to present the stimuli. The most widespread method is the use of monitors controlled by personal computers. Traditionally, most experiments used cathode-ray tubes but they are more and more difficult to access, and instead, liquid–crystal displays are getting more and more popular. The two types have fundamentally different working principles and limitations in displaying the stimulus. In our experiments, the temporal precision of the stimulus presentation was in focus. We investigated whether liquid–crystal displays, which are not considered to be fit to display fast successive stimuli, can represent an alternative choice for cathode-ray tubes. We used the double flash and the flicker illusion to compare the technical capabilities of the two monitor types. These illusions not only do require a precise timing but also a very short exposure to the stimuli. At the same time, the interstimulus interval is also of extreme importance. In addition, these illusions require peripheral stimulation of the retina, which is more sensitive to the temporal aspects of the visual stimulus. On the basis of previous studies and our own psychophysical results, we suggest that liquid–crystal displays might be a good alternative for precise, frame-to-frame stimulus presentation even if parts of the stimuli are projected on the peripheral retina.